Show Me Your Environment : Essays on Poetry, Poets, and Poems - Baker, David, 1954- (Book collections on Project MUSE., 2014)
"In Show Me Your Environment, a penetrating yet personable collection of critical essays, David Baker explores how a poem works, how a poet thinks, and how the art of poetry has evolved--and is still evolving as a highly diverse, spacious, and inclusive art form. The opening essays offer contemplations on the "environment" of poetry from thoughts on physical places and regions as well as the inner aesthetic environment. Next, Baker looks at the highly distinctive achievements and styles of poets ranging from George Herbert and Emily Dickinson through poets writing today. Finally, he takes joy in reading individual poems--from the canonical to the contemporary; simply and closely."--Publisher's description